Safety assessment and results of coronary spasm provocation testing in patients with myocardial infarction with unobstructed coronary arteries compared to patients with stable angina and unobstructed coronary arteries. Issue 4 (8th June 2020) - Probst, Sabine; Seitz, Andreas; Martínez Pereyra, Valeria; Hubert, Astrid; Becker, Alexander; Storm, Klaus; Bekeredjian, Raffi; Sechtem, Udo; Ong, Peter
Abstract: Background: Coronary spasm is an established cause for myocardial infarction with unobstructed coronary arteries, and can be diagnosed using intracoronary acetylcholine testing. However, it has been questioned whether such testing is feasible and safe in the acute phase. The aim of this study was to assess the frequency of coronary spasm and the safety of the acetylcholine test in patients with myocardial infarction with unobstructed coronary arteries compared to patients with stable angina and unobstructed coronaries. Methods: One hundred and eighty selected patients (52% women, mean age 62 ± 13 years) with either myocardial infarction with unobstructed coronary arteries ( n = 80) or stable angina and unobstructed coronaries ( n = 100) were enrolled from 2007–2018. All patients underwent the acetylcholine test according to a standardised protocol immediately after diagnostic angiography. Apart from assessment of clinical, demographic and risk factor data, side effects and complications during the acetylcholine test were recorded. Results: Overall, epicardial spasm was found in 26% with a higher prevalence among the myocardial infarction with unobstructed coronary arteries compared to the stable angina patients (35% vs 19%, p = 0.017). Microvascular spasm was found in 42% with a higher prevalence among the stable patients compared to the myocardial infarction with unobstructed coronary arteries cohort (53% vs 29%, p = 0.0014). There were no statistically significant differences in the rate of side effects (16% vs 14%, p = 0.674) or complications (1% vs 2.5%, p = 0.438) between the two groups. None of the patients experienced irreversible complications. Conclusion: Coronary spasm is a frequent cause for myocardial infarction with unobstructed coronary arteries. Spasm provocation testing using acetylcholine is feasible in such patients in the acute phase. The complication rate during acetylcholine testing in myocardial infarction with unobstructed coronary arteries patients is low and comparable to patients with stable angina.